Comprehensive analysis of 33 human cancers reveals clinical implications and immunotherapeutic value of the solute carrier family 35 member A2 - Xu, Shengshan; Chen, Xiguang; Fang, Jianxiong; Chu, Hongyu; Fang, Shuo; Zeng, Leli; Ma, Hansu; Zhang, Tianzhi; Chen, Yu; Wang, Tao; Zhang, Xin; Shen, Tao; et al. (Frontiers in Immunology, 2023)
Abstract Background: Solute carrier family 35 member A2 (SLC35A2), a member of the SLC35 solute carrier family of human nucleoside sugar transporters, shows emerging regulatory roles in multiple tumors. However, the panorama picture of the expression and prognosis value of SLC35A2 in cancers remains unknown. Materials and Methods: Expression levels of SLC35A2 mRNA and protein in different cancers were obtained from The Cancer Genome Atlas (TCGA) and Human Protein Atlas database (HPA). Differential expression of SLC35A2 in tumor and normal tissues or among clinical characteristics was then investigated, followed by assessing protein levels differences in 120 lung squamous cell carcinoma and 98 lung adenocarcinoma tissue microarrays by immunohistochemistry (IHC). Kaplan-Meier survival analysis and Cox regression were used to study the prognosis value of SLC35A2. The relationship between SLC35A2 expression and DNA methylation, genetic alterations, tumor mutation burden (TMB), microsatellite instability (MSI), and tumor microenvironment were explored with Spearman correlation analysis. Finally, the CellMiner database is used for gene-drug sensitivity analysis, and molecular docking is applied to predict potential drugs interacting with SLC35A2. Results: The expression of SLC35A2 was higher in a variety of tumor tissues than in corresponding normal tissues and was tightly associated with poor prognosis. It was associated with MSI, TMB, and immune cell infiltration. Conclusion: In summary, our study revealed that SLC35A2 is upregulated in 20 cancer types, including breast invasive carcinoma (BRCA), colon adenocarcinoma (COAD), lung adenocarcinoma (LUAD), and lung squamous cell carcinoma (LUSC). Higher expression of SLC35A2 is associated with poor prognosis in 5 cancer types, such as BRCA and COAD. Additionally, our analysis indicates that higher expression of SLC35A2 is positively correlated with reduced lymphocyte infiltration in 13 cancer types, including BRCA and COAD. Furthermore, by analyzing data from several clinical trials, it showed patients with LUAD, LUSC, SKCM, and BLCA who have higher expression of SLC35A2 may experience better response to immunotherapy. Therefore, our study proposes SLC35A2 as a potential predictive biomarker for prognosis and immunotherapy efficacy in a variety of tumors and neoplasms, providing a theoretical basis for further investigations into its prognostic and therapeutic potential.